2008
DOI: 10.1590/s1980-57642009dn20400004
|View full text |Cite
|
Sign up to set email alerts
|

Mild behavioral impairment: A prodromal stage of dementia

Abstract: Mild cognitive impairment (MCI) was defined by Petersen et al. (1999) as progressive memory loss, a prodrome of Alzheimer’s disease. MCI is a well-established entity that can be both a diagnosis in medical practice and a valid target of Alzheimer’s prevention therapy. More recently MCI has expanded to include other cognitive domains with other potential causes: amnestic MCI, multiple domains MCI, and single domain non-amnestic MCI. Behavioral symptoms in MCI are associated with a higher risk of dementia, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 29 publications
(23 reference statements)
1
57
0
Order By: Relevance
“…Although rates of progression are widely different across studies and populations, it has been found that the rate at which patients with cognitive impairment progress to dementia is about 70% over a period of 5 years, that is, 10%–15% per year as opposed to 1%-2% of control subjects [31]. Thus, its early detection is of great importance to develop preventive and early rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Although rates of progression are widely different across studies and populations, it has been found that the rate at which patients with cognitive impairment progress to dementia is about 70% over a period of 5 years, that is, 10%–15% per year as opposed to 1%-2% of control subjects [31]. Thus, its early detection is of great importance to develop preventive and early rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Of the latter patients, 36% had FTD, 28% had AD; 18% had VaD and 18% had other types of dementia16. As a result we proposed the syndrome of “Mild Behavioral Impairment” (MBI) consisting of: (1) persistent behavioral changes and mild psychiatric symptoms, especially disinhibition; (2) no serious cognitive complaints; (3) normal activities of daily living; and (4) absence of dementia16-18. MBI has been hypothesized to confer increased risk for dementia development, especially of FTD, whether or not significant cognitive symptoms are present.…”
Section: Introductionmentioning
confidence: 99%
“…For example we reported that in 50% of a series of dementia patients who consulted our service NPS were the first indication of change, before the occurrence of cognitive symptoms. Of the latter patients, 36% had FTD, 28% had AD; 18% had VaD and 18% had other types of dementia16. As a result we proposed the syndrome of “Mild Behavioral Impairment” (MBI) consisting of: (1) persistent behavioral changes and mild psychiatric symptoms, especially disinhibition; (2) no serious cognitive complaints; (3) normal activities of daily living; and (4) absence of dementia16-18.…”
Section: Introductionmentioning
confidence: 99%
“…The last presents as impairment in a single cognitive domain other than memory, such as a dysexecutive syndrome. This condition was described as mild behavioral impairment (MBI) and as MCI of the frontotemporal type 3,4 …”
Section: Criteria For Mild Behavioral Impairment (Mbi)3 Vascular Cmentioning
confidence: 99%